2010
DOI: 10.1007/s00213-010-1953-1
|View full text |Cite
|
Sign up to set email alerts
|

Attentional bias toward cigarette cues in active smokers

Abstract: Rationale-While it is well documented that substance users exhibit attentional bias toward addiction-related stimuli, the exact mechanism remains unclear.Objectives-To differentiate between distinct aspects of attentional allocation in the smoking-cue attentional bias observed in smokers.Methods-Active smokers (AS) and non-smoking controls completed spatial cueing tasks with pairs of smoking and neutral pictorial cues to measure attentional capture, and an attentional blink task with either a smoking or neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
32
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 77 publications
(112 reference statements)
5
32
2
2
Order By: Relevance
“…This process is often referred to as attentional bias and is based on the theory of incentive sensitisation put forth by Robinson and Berridge (7) . This theory has been applied to drugs of addiction (8) , smoking (9) and alcohol research (10) . More recently, it has been suggested that food-related stimuli may also have the ability to Proceedings of the Nutrition Society capture attention and activate reward pathways in the brain thus making visual food cues more salient to the observer (11,12) .…”
Section: Incentive Sensitisation: Weight Status: Eye Tracking: Visualmentioning
confidence: 99%
See 1 more Smart Citation
“…This process is often referred to as attentional bias and is based on the theory of incentive sensitisation put forth by Robinson and Berridge (7) . This theory has been applied to drugs of addiction (8) , smoking (9) and alcohol research (10) . More recently, it has been suggested that food-related stimuli may also have the ability to Proceedings of the Nutrition Society capture attention and activate reward pathways in the brain thus making visual food cues more salient to the observer (11,12) .…”
Section: Incentive Sensitisation: Weight Status: Eye Tracking: Visualmentioning
confidence: 99%
“…This process is often referred to as attentional bias and is based on the theory of incentive sensitisation put forth by Robinson and Berridge (7) . This theory has been applied to drugs of addiction (8) , smoking (9) and alcohol research (10) . More recently, it has been suggested that food-related stimuli may also have the ability to…”
mentioning
confidence: 99%
“…Some behavioral evidence suggests that attention is already drawn toward the addiction-related stimuli at very early (e.g., 50 ms; Noël et al, 2006) time periods. Furthermore, at around 200 ms, wherein reward-related attentional capture effects have been found (e.g., Donohue et al, 2016), two studies using smoking-related stimuli did find attentional capture by these images in smokers (Bradley, Field, Mogg, & De Houwer, 2004;Chanon, Sours, & Boettiger, 2010). Other studies, however, have not found such attentional capture at 200 ms (e.g., Bradley, Field, Healy, & Mogg, 2008), or have found it only in male participants (Perlato et al, 2014), leaving the question open as to how automatic the capture of attention by addiction-related stimuli may be.…”
mentioning
confidence: 98%
“…For example, Chanon, Sours, and Boettiger (2010) had cigarette smokers complete a visual probe task wherein two pictures -one smoking-related, the other neutral -were briefly displayed (i.e., for 150 or 500 milliseconds) prior to both disappearing and one being replaced by a small checkerboard. The participant's task was to report the location of the checkerboard.…”
Section: Attentionmentioning
confidence: 99%
“…Reaction times were shorter when the checkerboard replaced the smoking-related pictures, suggesting a bias towards the smoking-related stimuli. This attentional bias for addiction-related stimuli has been demonstrated in smokers (Bradley, Field, Mogg, and De Houwer, 2004;Cane, Sharma, and Albery, 2009;Chanon, Sours, and Boettiger, 2010;Drobes, Elibero, and Evans, 2006;Ehrman et al, 2002;Mogg, Bradley, Field, and de Houwer, 2003;Munafo et al, 2003;Waters et al, 2003), alcohol abusers (Cox, Blount, and Rozak, 2000;Johnsen et al, 1994;Jones, Bruce, Livingstone, and Reid, 2006;Lusher, Chandler, and Ball, 2004;Stetter et al, 1995;Stormark, Field, Hugdahl, and Horowitz, 1997), problem drinkers (Sharma, Albery, and Cook, 2001), cocaine addicts (Copersino et al, 2004), cocaine users (Hester, Dixon, and Garavan, 2006; but see Montgomery et al, 2010), opioid addicts (Franken, Kroon, Wiers, and Jansen, 2000;Lubman et al, 2000), and cannabis users (Cane, Sharma, and Albery, 2009;Field, Eastwood, Bradley and Mogg, 2006). Additionally, greater attentional bias towards food-related stimuli has been found in obese children (Braet and Crombez, 2003), obese adult females (Castellanos et al, 2009;Nijs, Muris, Euser, and Franken, 2010;Werthmann et al, 2011), and formerly obese individuals (Phelan et al, 2011) relative to healthy weight controls (see Soetens and Braet, 2007, for an exception).…”
Section: Attentionmentioning
confidence: 99%